Spacial differentiation on the intraurban scale: analysis of the civil construction industry impacts to Mossoró City: - Silva Beserra, Fábio Ricardo; Pereira Júnior, Edilson (Geografares, 2020)
This article aims to interpret the spatial differentiation in the intraurban scale, without forgetting that for this it is necessary to translate the economic and social division of space, analyzing processes, functions and content-forms from the land use patterns that define central and peripherals zones and sectors in the city. Elements of empirical validation are selected from the materialized phenomena in Mossoró/RN, a medium-sized city in the Brazilian northeast, where an important urban restructuring (caused by the expansion of the civil construction industry from the 2000s on) redefined the economic dynamics, resulting in transformations in the traditional spatial order. The intention is to investigate the new geographies of the city from the latest real estate deals and their impacts on the urban fabric, reaching the mosaic of social areas, identified from the combination of attributes defined by different socioeconomic statuses.